1997
DOI: 10.1002/(sici)1099-1026(199703)12:2<55::aid-ffj615>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Derivatives in GC Separation of Racemic Mixtures of Volatiles. Part XI. Some Applications of Cyclodextrin Derivatives in GC Enantioseparations of Essential Oil Components

Abstract: Cyclodextrin derivatives (CDDs) are successful GC enantioselective stationary phases to evaluate essential oils through the enantiomeric composition of their optically active components. The most recent CDDs have greatly enlarged the number of separable racemates and, in many cases, it is now possible to evaluate origin and genuineness of an essential oil through several of its optically active components in a single GC run. Applications of this approach to lavender, lemon, peppermint, rose and iris oils are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…They have already demonstrated that any isomerization was provoked in both compounds when acetylated separately. The α value was higher than the α obtained in some α , β , and γ permethylated cyclodextrins [ 13 , 33 ] and in stationary GC phases of other cyclodextrin derivatives [ 39 41 ].…”
Section: Resultsmentioning
confidence: 69%
“…They have already demonstrated that any isomerization was provoked in both compounds when acetylated separately. The α value was higher than the α obtained in some α , β , and γ permethylated cyclodextrins [ 13 , 33 ] and in stationary GC phases of other cyclodextrin derivatives [ 39 41 ].…”
Section: Resultsmentioning
confidence: 69%